劳役与性别——里耶秦简所记载的刑徒分工 - Lim Hoei Shian (Sinolingua: Journal of Chinese Studies, 2025)
Traditional historical sources generally hold that system of penal nomenclature originated from convict labor types. With gender distinctions in Qin-Han penal nomenclature, this implies a corresponding clear gender-based labor division—for example, chengdan (wall-builder)/chong (grain-pounder) and guixin (gatherer of fuel for the spirits)/baican (white-rice sorter) were assigned different tasks—though traditional texts lack explicit details on lichen (male convict servants) and liqie (female convict servants) specific duties. The Shuihudi Qin bamboo manuscripts partially revealed these convicts’ actual work, showing their labor scope was less restricted than traditionally depicted, not limited solely by penal status. In the past decade, Liye Qin “tubu” (convict labor registers) have further clarified convict labor and its organization: scholarly studies indicate no significant labor intensity differences among lichen/liqie, guixin/baican, and chengdan/chong, with diverse work and common male-female co-labor, though some tasks were gender-exclusive (an understanding subject to new material releases). In summary, while traditional sources emphasize distinct gender-based labor division and “inner-outer” separation for convicts, Liye’s excavated materials—especially tubu—demonstrate gender did not significantly differentiate convict labor, partially challenging the traditional rigid “inner-outer” labor barrier.